Improvement of Overall Survival Using TKIs as Salvage Therapy in Advanced Thyroid Carcinoma: Real-Life Data on a Single Center Experience - Brilli, Lucia (J Clin Med, 2021)
Background: Tyrosine kinase inhibitors (TKIs) have improved progression-free survival in patients with advanced thyroid cancer. So far, few studies have investigated the efficacy of TKIs in a second-line setting. The purpose of our study was to explore the salvage therapy efficacy in patients with advanced thyroid cancer. Methods: We retrospectively evaluated 63 patients with progressive advanced thyroid carcinoma treated with TKIs divided into a Study group (23 patients) treated with salvage therapy, and a Control group (40 patients) treated with only one TKI. Results: Similar clinical benefits (stable disease + partial response) and progression free survival between the first and the second line TKI were observed in the Study group (p > 0.99 and p = 0.5, respectively). Median overall survival (OS) was 67.7 months in the Study group and 22.6 months in the Control group (HR 2.46; 95% CI 1.34–4.52, p = 0.004). After stratifying the whole population by age (<65 and ≥65 years), OS was significantly different (p < 0.001) with the best survival curve in younger patients, treated with salvage therapy and the worst in older subjects, treated with only one TKI. Conclusions: Salvage therapy showed a significant improvement of OS in patients with advanced thyroid cancer who experienced disease progression during prior TKI therapies.